The role of accountability in federal acquisition: A search for context. Issue 4 (1st March 2015) - Fox, Dan; Morris, John C.
Abstract : The issue of accountability in the federal government's acquisition process has been the topic of much discussion and investigation. While few argue that accountability is unimportant, it remains largely unexplored in the context of the acquisition process. This paper seeks to examine the acquisition process in some detail, and analyze the role of accountability in that process. We conclude with some broader observations about accountability in federal acquisition, and directions for future research.